Analisis SIMRS Terhadap Peningkatan Pelayanan Kesehatan Di Era Digital Dalam Mendukung Implementasi Rekam Medis Elektronik - Cepi Hidayatuloh; Dety Mulyanti (Pusat Riset dan Inovasi Nasional, 2023)
HIMS is a solution for hospitals for digital transformation. HIMS is also a strategic step in improving the quality of health services. With HIMS where the data will be better organized and integrated, besides that it makes administrative processes and other data management in the hospital easier and more efficient. The purpose of this study is to find out how HIMS can improve health services. The method used is a theoretical study by analyzing and comparing existing theories. The results of this study are that HIMS in hospitals also provides many benefits in increasing the efficiency and quality of health services. Implementation in EMR with treatment information management, statistical data research, administrative evidence, financing and service quality improvement. It can be concluded that HIMS can improve a health service. HIMS is also an indicator of good and efficient data storage and is included in the health service quality component. In the digitalization era, hospital agencies aim to avoid unwanted errors, such as incorrect data input, failed integration, human error, and slow information. So that the information system that facilitates the hospital can be a reference for the rate of business growth and the development of hospital information technology. Hospital Agencies are expected to always develop new management information systems in accordance with the times. With HIMS, hospital services will be more optimal because they are already digital-based. Digitalization exists because of increasingly advanced technological developments.